Ecclesiastes - Goldingay, John. (Eugene, Oregon : : Cascade Books, 2021)
"Ecclesiastes is the most surprising book in the Scriptures. It challenges its readers to reconsider what they think life is about and how far it is possible to understand God's involvement in the world. This commentary seeks to help people enter the world of Ecclesiastes and see how it can increase their understanding of God and of themselves."--Publisher.
Includes bibliographical references (pages 1-24) and indexes.
Keywords: Bible. -- Commentaries; Bible. Ecclesiastes -- Commentaries